Gut Microbial Succession Patterns and Metabolic Profiling during Pregnancy and Lactation in a Goat Model - Ke Zhang; Gongwei Liu; Yujiang Wu; Ting Zhang; Mengmeng Guo; Yu Lei; Xi Cao; Langda Suo; Daniel Brugger; Xiaolong Wang; Yuxin Yang; Yulin Chen (Microbiology Spectrum, 2023)
ABSTRACT The maternal gut microbiome affects the duration of pregnancy, delivery, and lactation. It also coordinates the stability of maternal metabolism by regulating and modulating inflammatory cytokines and reproductive hormones. This has been shown in several species; however, the situation in ruminants remains a black box. Here, we aimed to elucidate the relationship between the hindgut microbiota, metabolism, and reproductive hormones in domestic goats (Capra hircus) during nonpregnancy, pregnancy, and lactation stages. The hindgut microbiota was altered during these three stages, with a drastic decrease in the abundance of Family_XIII_AD3011_group in the second and third trimesters of pregnancy. Additionally, a decline in the abundance of Christensenellaceae_R-7_group and Turicibacter was observed from the nonpregnancy stage to late gestation. Family_XIII_AD3011_group and Paeniclostridium were strongly correlated with decreased fecal estradiol and progesterone. Furthermore, we generated a metabolome atlas of the gut and serum from nonpregnancy to lactation to reveal the specific metabolic fingerprints of each physiological stage. Several specific gut metabolites, including carnitine C8:1, γ-aminobutyric acid, and indole-3-carboxylic acid, were negatively correlated with the fecal and serum estradiol concentrations. In contrast, 2′-deoxyinosine, deoxyadenosine, and 5′-deoxyadenosine were positively correlated with the fecal and serum estradiol concentrations. The levels of 2′-deoxyinosine, deoxyadenosine, and 5′-deoxyadenosine in fecal samples were positively correlated with Family_XIII_AD3011_group. Other serum metabolites, such as (±)12-HEPE (hydroxy eicosapentaenoic acid), (±)15-HEPE, (±)18-HEPE, cytidine, uracil, and 5-hydroxyindole-3-acetic acid, were negatively correlated with the serum concentrations of estradiol and progesterone. Finally, Corynebacterium and Clostridium_sensu_stricto_1 in the fecal samples were positively correlated with the abundance of 11,12-EET (epoxy-eicosatrienoic acid), (±)18-HEPE, (±)15-HEPE, and (±)12-HEPE in the serum. IMPORTANCE Our findings revealed that the activity of Family_XIII_AD3011_group and Corynebacterium is strongly correlated with the beneficial regulation of physiological hormones and metabolic changes during pregnancy and lactation. These findings are key for guiding targeted microbial therapeutic approaches to modulate microbiomes in gestating and lactating mammals.